2016
DOI: 10.1055/s-0042-101854
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic resection of subtotal or completely circumferential laterally spreading colonic adenomas: technique, caveats, and outcomes

Abstract: Endoscopic resection of C-LSL is feasible and safe. Minor residual adenoma is common but endoscopically treatable with long-term cure. Symptomatic stricturing amenable to balloon dilation may occur. Empiric surgical referral for C-LSL based on extensive circumferential involvement may be avoided.ClinicalTrials.gov NCT01368289.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…The patient had also received radiotherapy for prostate cancer in the past which may have contributed to the development of stenosis with a less extensive defect. Also, in keeping with other studies, we found that several patients with stenosis were asymptomatic [3][4][5][6]. Interestingly, we found that stenosis in such patients generally improves spontaneously with evident improvement at subsequent surveillance endoscopy and none progressed to develop symptoms.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The patient had also received radiotherapy for prostate cancer in the past which may have contributed to the development of stenosis with a less extensive defect. Also, in keeping with other studies, we found that several patients with stenosis were asymptomatic [3][4][5][6]. Interestingly, we found that stenosis in such patients generally improves spontaneously with evident improvement at subsequent surveillance endoscopy and none progressed to develop symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…However, 1 patient with only 50% circumference defect at the rectosigmoid developed an asymptomatic stenosis. The patient had diverticulosis and Tutticci et al have postulated diverticular disease with luminal narrowing may play a role in the development of stenosis [6]. The patient had also received radiotherapy for prostate cancer in the past which may have contributed to the development of stenosis with a less extensive defect.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations